Meta-analysis of comparative clinical outcomes between primary closure and T-tube drainage following laparoscopic common bile duct exploration and extraction combined with cholecystectomy - WANG Ping, BAO Hui, SONG Zhenshun (Waike lilun yu shijian, 2025)
Objective To systematically evaluate the comparative efficacy of primary closure versus T-tube drainage following laparoscopic common bile duct exploration (LCBDE) and extraction combined with cholecystectomy in the management of choledocholithiasis with concomitant cholecystolithiasis.Methods A comprehensive search of databases including PubMed, CNKI, Wanfang, and VIP was conducted from January 1, 2012, to December 31, 2021. Eligible studies were screened based on predefined inclusion/exclusion criteria, and meta-analysis was performed using Review Manager 5.4 software.Results Ten studies involving 1 589 patients (783 primary closure vs. 806 T-tube drainage) were included. Meta-analysis demonstrated that primary closure significantly reduced operation time [MD = -15.59, 95% CI: (-23.74, -7.45), P = 0.000 2], intraoperative blood loss [MD = -6.49, 95% CI: (-12.74, -0.24), P = 0.04], postoperative gastrointestinal recovery time [MD = -0.39, 95% CI: (-0.60, -0.19), P= 0.000 2], postoperative hospital stay [MD = -1.41, 95% CI: (-2.19, -0.62), P = 0.000 4], and hospitalization costs [SMD = -0.66, 95% CI: (-1.21, -0.12), P = 0.02].Conclusions Both closure methods are safe and effective for choledocholithiasis with cholecystolithiasis. However, primary closure offers advantages including shorter operative duration, reduced blood loss, decreased hospital stay, and lower costs, warranting broader clinical adoption.